Prevalence of Carpal Tunnel Syndrome among Dentists of Faisalabad - Hafiza Mubashra, Mariam Mehmood, Shomaila Malik, Hijab Zahra, Ayesha Mehmood, Shanzay Mukhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dentists in their practice are daily exposed to work-related vibrations. The important cause of work disability is carpal tunnel syndrome. Methods: In this cross-sectional study data from 100 dentists was collected using convenient sampling technique. Prior to data collection consent form was sent to the respective dental section of government hospitals of Faisalabad. The dentists who met the inclusion criterion were invited to participate in the study. The Diagnosis was made according to clinical tests of Phalen and Tinel. Age, sex, years of experience, working hours per week and the type of procedure were then be considered as dependent variables Results: Overall, prevalence rate of 60% of carpal tunnel syndrome among old aged dentists was observed. Conclusion: The risk of carpel tunnel syndrome increases with age. It also concluded that 60% prevalence rate was found in the dentists. Older dentists of age 35-50 year were included in more risk group than younger 20-25 year. Keywords: Carpal tunnel syndrome, Phalen’s sign, Tinel’s sign, endodontic file